Orthogonal dual-modification of proteins for the engineering of multivalent protein scaffolds - Mühlberg, Michaela; Hoesl, Michael G.; Kuehne, Christian; Dernedde, Jens; Budisa, Nediljko; Hackenberger, Christian P. R. (Beilstein Journal of Organic Chemistry, 2015)
To add new tools to the repertoire of protein-based multivalent scaffold design, we have developed a novel dual-labeling strategy for proteins that combines residue-specific incorporation of unnatural amino acids with chemical oxidative aldehyde formation at the N-terminus of a protein. Our approach relies on the selective introduction of two different functional moieties in a protein by mutually orthogonal copper-catalyzed azide–alkyne cycloaddition (CuAAC) and oxime ligation. This method was applied to the conjugation of biotin and β-linked galactose residues to yield an enzymatically active thermophilic lipase, which revealed specific binding to Erythrina cristagalli lectin by SPR binding studies.
Keywords: chemoselectivity; dual protein modification; lectin; multivalency